2021
DOI: 10.1002/emp2.12572
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia management in the emergency department: An expert panel consensus

Abstract: Hyperkalemia is a common electrolyte abnormality identified in the emergency department (ED) and potentially fatal. However, there is no consensus over the potassium threshold that warrants intervention or its treatment algorithm. Commonly used medications are at best temporizing measures, and the roles of binders are unclear in the emergent setting. As the prevalence of comorbid conditions altering potassium homeostasis rises, hyperkalemia becomes more common, and hence there is a need to standardize manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(55 citation statements)
references
References 58 publications
(138 reference statements)
0
50
0
2
Order By: Relevance
“…No consistent thresholds for potassium levels warranting treatment have been proposed. [3] First, higher serum potassium is associated with higher mortality. A retrospective multicenter study revealed that higher serum potassium levels, severe underlying diseases, and developing acute kidney injury (AKI) from normal baseline renal function were associated with higher mortality.…”
Section: Thresholds For Initiating Treatment Of Hesmentioning
confidence: 99%
See 4 more Smart Citations
“…No consistent thresholds for potassium levels warranting treatment have been proposed. [3] First, higher serum potassium is associated with higher mortality. A retrospective multicenter study revealed that higher serum potassium levels, severe underlying diseases, and developing acute kidney injury (AKI) from normal baseline renal function were associated with higher mortality.…”
Section: Thresholds For Initiating Treatment Of Hesmentioning
confidence: 99%
“…[6] Second, electrocardiogram (ECG) changes indicate higher risk of mortality in hyperkalemia. [3,7] Elevated serum potassium in cardiac myocytes results in cardiac instability inducing ventricular fibrillation and cardiac arrest. [8] Higher mortality occurs in patients with serum potassium ≥6.0 mmol/L possessing new ECG changes than those without ECG changes.…”
Section: Thresholds For Initiating Treatment Of Hesmentioning
confidence: 99%
See 3 more Smart Citations